Biochemistry of iron associated with pyritization in Holocene marshes, Mar Chiquita, Buenos Aires, Argentina - Osterrieth, Margarita (2016)
In salt marshes, the hydrodynamics and the availability of iron, organic matter and sulphate, influence the formation and/or dissolution of iron sulfides and iron oxyhydroxides. Therefore, they constitute key factors affecting the iron biogeochemical processes in these environments. The aim of this work is to evaluate the physicochemical and mineralogical variations associated to iron biogeochemistry in palaeo and actual salt marshes in the area of influence of the Mar Chiquita coastal lagoon, Pampean Plain, Argentina. In soils of exhumed palaeo marshes, the iron contents are 56–95 lmol g-1, whereas these contents decrease to 36–75 lmol g-1 in actual marsh soils. The presence of framboidal and poliframboidal pyrites associated with gypsum, barite, calcite, halite and iron oxyhydroxides defines the conditions of the pedosedimentary sequences of the Holocene paleomarshes. Sequences of pyrite formation (sulfidization) and degradation (sulfuricization) were observed. These processes were evidenced by a sequential extraction, reflecting that the largest proportion of iron is in the form of crystalline iron oxides (28–76 %) and lepidocrocite (6–16 %); while the proportion associated with ferrihydrite and pyrite is low (0–9 and 1–17 %, respectively). These facts could be partly explained by the complex redox processes characteristic of these environments, such as aeration generated by the rhizosphere and intense bioturbation by invertebrates. These iron biomineralizations have been useful because they allow paleoenvironmental interpretations and characterization of paleomarshes, and environmental inferences related to the management of actual salt marshes.